2017
DOI: 10.17098/amj.365482
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Cervical Cytology Results in a Tertiary Health Centre Between 2006-2015

Abstract: Objectives: The main goal of cervical cancer cytologic screening is to prevent mortality and morbidity associated with cervical cancer. We aimed to retrospectively evaluate the prevalence of cervical cytological abnormalities in patient records obtained from electronic data at our tertiary hospital. Materials and Methods: Demographic characteristics and data on cervical cytological abnormalities were evaluated from patients (n=54999) who underwent Pap tests in our hospital from 2006 to 2015. Results: Data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In studies in Turkey, positivity rates in cervical cytology reported as 1.8% -8.6%. [17][18][19][20][21][22][23][24] In a multicenter study that can be representative throughout Turkey, ratios that was reported by the participating centers ranged from 0.3 to 16.6%. According to the type of participant centers, average values are 2.81% in State Hospitals, 3.16% in University Hospitals and 12.32% in Private Hospitals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies in Turkey, positivity rates in cervical cytology reported as 1.8% -8.6%. [17][18][19][20][21][22][23][24] In a multicenter study that can be representative throughout Turkey, ratios that was reported by the participating centers ranged from 0.3 to 16.6%. According to the type of participant centers, average values are 2.81% in State Hospitals, 3.16% in University Hospitals and 12.32% in Private Hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…These rates have been reported by various studies published in Turkey between 2.25% and 12.6%. 15,[17][18][19][20][21][22][23][24] In two separate studies that may reflect the Turkey-wide situation, the ratios are reported as 1.8% and 2.87%. 14,17 The ASC / SIL ratio in our study is 1.89% and it is in acceptable limits.…”
Section: Discussionmentioning
confidence: 99%